Problems for the study of regional history: The case of Cusco - Glave, Luis Miguel (1980)
Whoever visits Cusco today will be able to verify, with a slight perception of daily events, that a regional feeling survives in its inhabitants, which seems to be a common characteristic of other regional centers such as Arequipa, Iquitos or Huánuco, to mention a few examples. It is enough to tune into a radio hearing to alternatively hear slogans such as: "Cusco is a city called for better destinations", or "Cusco can only be developed with effective decentralization". Any regional problem will find in the radio comments the common cause of all: Lima's centralism.